PROBLEMS OF THE LAW ENFORCEMENT PRACTICE OF COURTS OF GENERAL JURISDICTION, WHICH ARISE WHEN CONSIDERING THE CONCLUSIONS SET OUT IN THE DECISIONS OF THE SUPREME COURT, AS WELL AS THE MODEL THEIR RESOLUTION - Хомутецький, Даниїл; Угриновська, Оксана (Київський національний університет імені Тараса Шевченка, 2024)
Background. In accordance with the norms of national legislation, the conclusions of the Supreme Court regarding the application of certain norms of law must be taken into account by courts of general jurisdiction when applying such norms of law. Thus, the article addresses the theoretical and legal analysis of the institution of legal opinion of the Supreme Court as a unique act of law enforcement in the national judicial system. Methods. The empirical scientific method (observation) was used in the part of the study of the practice of taking into account conclusions from the Supreme Court decisions by the courts; theoretical and scientific methods (proposing hypotheses and theories, analysis, synthesis, abstraction) in the part of identifying categories of improper (defective) consideration of conclusions from the Supreme Court decisions. The method of scientific modeling is used in the part of determining ways to solve the problematic issues raised in the article. Results. Emphasis is placed on the problem of the insufficiency of the definitions in relation to legal regulation of the legal opinion of the Supreme Court. The article highlights problematic issues related to taking into account the conclusions from the decisions of the Supreme Court: 1) the problem of dividing such conclusions into those that directly affect the outcome of the proceedings, and those that do not have such an impact on the outcome; 2) the problem of taking into account the conclusions expressed without due consideration of the actual circumstances and/or legislation; 3) the problem of the defectiveness of conclusions relating to legal prescriptions that have lost their validity or have been changed, and conclusions from which the Supreme Court deviated; 4) the problem of taking into account conclusions from Supreme Court decisions retrospectively (backward in time). The analysis of the indicated problems was carried out on the basis of theoretical provisions, court practice and partially foreign experience of law enforcement. Conclusions. Based on the practice of courts of general jurisdiction, the practice of the Supreme Court on the above-mentioned problems, attention is focused on cases of formal consideration of conclusions from Supreme Court decisions, own conclusions are put forward and models for solving problematic issues are proposed.

Вступ. Відповідно до норм національного законодавства висновки Верховного Суду щодо тих чи інших норм права мають ураховуватись судами загальної юрисдикції при їх застосуванні. Отже, статтю присвячено теоретико-правовому аналізу інституту правового висновку Верховного Суду як унікального акту правозастосування в національній судовій системі, а також пошуку шляхів оптимізації процесу врахування таких висновків при розв'язанні судами інших справ. Методи. Використано емпіричний науковий метод (спостереження) у частині дослідження практики врахування судами висновків із постанов Верховного Суду, теоретичні наукові методи (висування гіпотез і теорій, аналіз, синтез, абстрагування) у частині виділення категорій неналежного (дефектного) урахування висновків із постанов Верховного Суду. У частині визначення шляхів розв'язання проблемних питань, що піднімаються у статті, застосовано метод наукового моделювання. Результати. Зроблено акцент на проблемі недостатності дефінітивного апарату стосовно юридичної регламентації правового висновку Верховного Суду. Виокремлено такі проблеми, пов'язані з урахуванням висновків із постанов Верховного Суду: 1) розподілу зазначених висновків на ті, що безпосередньо впливають на результат розгляду, і ті, що не мають такого впливу на результат розв'язання справи, у якій вони висловлені; 2) урахування висновків, що висловлені без належного взяття до уваги фактичних обставин та/або норм права; 3) дефектності висновків, що стосуються норм права, які втратили чинність або були змінені, і висновків, від яких відступив Верховний Суд; 4) урахування висновків із постанов Верховного Суду ретроспективно (зворотно у часі). Проаналізовано вказану проблематику на основі теоретичних положень, судової практики й частково – на основі іноземного досвіду правозастосування. Висновки. На основі практики судів загальної юрисдикції, а також Верховного Суду, щодо зазначених вище проблем зосереджено увагу на випадках формального врахування висновків із постанов Верховного Суду, висунуто власні тези й запропоновано моделі розв'язання проблемних питань.
ПРОБЛЕМАТИКА ПРАВОЗАСТОСОВНОЇ ПРАКТИКИ СУДІВ ЗАГАЛЬНОЇ ЮРИСДИКЦІЇ, ЩО ВИНИКАЄ ПРИ ВРАХУВАННІ ВИСНОВКІВ, ВИКЛАДЕНИХ У ПОСТАНОВАХ ВЕРХОВНОГО СУДУ, А ТАКОЖ МОДЕЛІ ЇЇ РОЗВ'ЯЗАННЯ
Keywords: висновок Верховного Суду; подібність правовідносин; відступ від правового висновку; дефектність висновків; проблеми врахування висновків; conclusion of the Supreme Court; similarity of legal relations; deviation from legal conclusion; defectiveness of conclusions; problems of taking into account conclusions